Herbal medicine for the management of COVID-19 during the medical observation period: A review of guidelines - Ang, Lin (Integr Med Res, 2020)
BACKGROUND: Medical observation period is a period of 14 days after any exposure to coronavirus disease 2019 (COVID-19) occurred. This review aimed to summarize and analyze the herbs and herbal formulae recommended by available guidelines. METHODS: A total of 14 sources were searched for potential guidelines that provide herbal medicine treatment for the medical observation period of COVID-19. We summarized and analyzed the recommended herbal formulae and performed a network analysis to identify the relationship between herbs. RESULTS: We found 9 guidelines that provide herbal formula for medical observation based on clinical manifestation. There are 12 herbal formulae with a total of 53 herbs recommended by the guidelines. The result of our network analysis showed that the herb Citri Reticulatae Pericarpium (Chen Pi) strongly paired with the herb Glycyrrhizae Radix et Rhizoma (Gan Cao). CONCLUSION: This review briefly summarized the usage of herbal medicine for the medical observation period of COVID-19 and may serve as a reference for future studies. More research is needed in the future to provide evidence on the usage of herbal medicine in various phases of COVID-10.